Presidential Authority in Granting Amnesty and Abolition: Constitutional Analysis of The Hasto Kristiyanto and Tom Lembong Cases - Novel, Mochamad; Muzakki, Raffa Misbach; Dhiaulhaq, Farras Zakka; Furanis, Franco Fabianus; Rusdiyanto, Sanika Daffa Raihan (Devotion : Journal of Research and Community Service, 2025)
The President's authority to grant amnesty and abolition is a constitutional prerogative with profound implications for the rule of law and the system of checks and balances. This article analyzes the implementation of such authority in the context of the Hasto Kristiyanto and Tom Lembong cases, both of which highlight the tension between law, politics, and public morality. Using a normative juridical and constitutional approach, the study examines the limits and mechanisms of the President's prerogative as regulated in Article 14 (2) of the 1945 Constitution and its implementing laws. Findings show that although the President holds prerogative power, it is not absolute, since it requires consideration by the House of Representatives as part of democratic oversight. The cases demonstrate how political decisions can risk legal legitimacy if not conducted with transparency and accountability. The study concludes that procedural reform of amnesty and abolition is necessary to align with the principles of modern constitutionalism, including the establishment of objective parameters, public hearing mechanisms, and strengthening legislative oversight to prevent abuse of executive power.